Information System Design Website-Based Packaging Box Ordering - Handini Widyastuti; Riswandi Ishak; Husni Mubarok; Fattya Ariani; Ade Christian (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
Currently many people are interested in entrepreneurship in various fields by using the sophistication of information technology. This has become a phenomenon and a huge business opportunity, one of which is Box Packaging. The need for packaging a product every day is increasing. The main function of a packaging is to protect the product so it is not easily damaged. The waterfall model provides a sequential or sequential software lifeflow approach starting from analysis, design, coding, testing and support stages to make it easier for management to report the results every month, provides information and understanding in designing ordering systems. As a result to search for a problem on the web. Can find out how the manufacturing process and materials to make a box. With this web- based packaging box ordering information system, it can make it easier for admins and customers to process packaging box orders. Because the application is equipped with online ordering so that the admin can easily manage customer data. It is hoped that it will make it easier for the admin so that purchase and payment transactions are stored more securely so as to minimize loss of customer data and customers can also consult packaging boxes first so that they are according to their wishes.